?ACHIEVEMENTS IN BENEFICIATION AND PROCESSING OF LOW GRADE GRAPHITE DEPOSITS, EGYPT (Biological Sciences - PJSIR, 1996)
Beneficiation of low graphite deposits sampled for Barramiya, Bent Abu Garriya and Wadi Sitra was carried out through systematic notation experiments using a mixture of (2-ethyl hexanol and hydrocarbon oil) as a collector in addition to several cationic and anionic co-collectors added to the collector mixture to improve flotation rate. It ap- pearsthat notation ratecouldbe increasedwhenethoxylated sulfonateused as anionicco-collector as wellaswhen the selectivity of graphite concentrate is increased. Processing of graphite concentrate which was carried out through roasting with sodium hydroxide and leaching with hydrochloric acid led to production of concentrate analyzing 92% fixedcarbon which meets theraw materialstandard forthe manufactureofcarbonelectrode andelectrochemical cells.